11-3k=-4(1+2k)

Simple and best practice solution for 11-3k=-4(1+2k) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11-3k=-4(1+2k) equation:


Simplifying
11 + -3k = -4(1 + 2k)
11 + -3k = (1 * -4 + 2k * -4)
11 + -3k = (-4 + -8k)

Solving
11 + -3k = -4 + -8k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '8k' to each side of the equation.
11 + -3k + 8k = -4 + -8k + 8k

Combine like terms: -3k + 8k = 5k
11 + 5k = -4 + -8k + 8k

Combine like terms: -8k + 8k = 0
11 + 5k = -4 + 0
11 + 5k = -4

Add '-11' to each side of the equation.
11 + -11 + 5k = -4 + -11

Combine like terms: 11 + -11 = 0
0 + 5k = -4 + -11
5k = -4 + -11

Combine like terms: -4 + -11 = -15
5k = -15

Divide each side by '5'.
k = -3

Simplifying
k = -3

See similar equations:

| xa=d | | 56=-1+3x | | 7(2a-8)+6=-92 | | 5-9a-14/3(2a) | | Z=-5z | | 2x^3-4x^2= | | 2l+6=6-10 | | Y-2+3x=6+5x | | 1/2x-y=3 | | 4x-(2x-10)=2x-6 | | sqrtx+2=3 | | 12x+10=14x | | -5(3-q)+4=5q | | 5(b+1)-6=2b-16 | | 8.364km= | | 1/3=4/6q | | 2y+3(0)y=10-0 | | 6m-2=-2-7m-m | | 15(x-3)=105 | | 3/4-3/4=0 | | -8(-2b+2)=-128 | | -8(1-4p)=120 | | 6t+3(5+-4)=12(2+-5) | | 6+2(33-x)-3+x= | | (25x)/45=-67 | | 2(5x-6)-3(1-x)=4-6(x+2) | | 5/7÷1/3 | | 12-3(4w-1)=7w-3(7+w) | | 2x+7-3x=6x-1 | | 6-2x-1=4x+6-6x-3 | | -(5b-1)=5b-(b-4) | | 7y^2-68y-20=0 |

Equations solver categories